Bioassay-Guided Isolation of Anti-Candida Biofilm Compounds From Methanol Extracts of the Aerial Parts of Salvia officinalis (Annaba, Algeria) - Kerkoub, Neila; Panda, Sujogya Kumar; Yang, Ming-Rong; Lu, Jing-Guang; Jiang, Zhi-Hong; Nasri, Hichem; Luyten, Walter (Frontiers in Pharmacology, 2018)
Salvia officinalis is frequently used in traditional Algerian medicine to treat diverse microbial infections, including oral and vaginal candidiasis. The aerial parts of S. officinalis collected in Annaba, Algeria were extracted in parallel by maceration with four solvents viz. hexane, acetone, methanol and water. All the extracts were tested in vitro against several Candida species: C. albicans, C. glabrata and C. parapsilosis. Furthermore, the activity against biofilm-forming C. albicans was investigated using bioassay-guided fractionation. A large-scale extract was prepared via maceration in methanol, followed by fractionation on a silica gel column using increasingly polar mixtures of n-hexane, ethyl acetate, methanol and acetic acid as mobile phase, to yield a total of 150 fractions. Two major active fractions (F-31 and F-39), were further separated by HPLC, resulting in several active chromatographic peaks. Carnosol and 12-methoxy-trans-carnosic acid were isolated as two major active compounds, and identified by a combination of NMR and mass spectrometry. The biofilm inhibitory concentration showed that 12-methoxy-trans-carnosic acid is more effective than carnosol with BIC50 values of 94 µM (95% confidence interval, 78.9 to 112.1 µM) and 314 µM (95% confidence interval, 200.7 to 491.2 µM), respectively. The present study supports the traditional use of sage in the treatment of various fungal infections caused by Candida. Further studies of the bioactive compounds in an in vivo Candida biofilm model are required to validate their clinical potential as antifungals.